The role of interstitial brachytherapy in the management of primary radiation therapy for uterine cervical cancer - Murakami, Naoya; Kobayashi, Kazuma; Kato, Tomoyasu; Nakamura, Satoshi; Wakita, Akihisa; Okamoto, Hiroyuki; Shima, Satoshi; Tsuchida, Keisuke; Kashihara, Tairo; Harada, Ken; Takahashi, Kana; Umezawa, Rei; et al. (Journal of Contemporary Brachytherapy, 2016)
Purpose : The aim of this study was to report the clinical results of uterine cervical cancer patients treated by primary radiation therapy including brachytherapy, and investigate the role of interstitial brachytherapy (ISBT). Material and methods: All consecutive uterine cervical cancer patients who were treated by primary radiation therapy were reviewed, and those who were treated by ISBT were further investigated for clinical outcomes and related toxicities. Results : From December 2008 to October 2014, 209 consecutive uterine cervical cancer patients were treated with primary radiation therapy. Among them, 142 and 42 patients were treated by intracavitary and hybrid brachytherapy, respectively. Twenty-five patients (12%) were treated by high-dose-rate (HDR)-ISBT. Five patients with distant metastasis other than para-aortic lymph node were excluded, and 20 patients consisted of the analysis. Three-year overall survival (OS), progression-free survival (PFS), and local control (LC) rate were 44.4%, 38.9%, and 87.8%, respectively. Distant metastasis was the most frequent site of first relapse after HDR-ISBT. One and four patients experienced grade 3 and 2 rectal bleeding, one grade 2 cystitis, and two grade 2 vaginal ulcer. Conclusions : Feasibility and favorable local control of interstitial brachytherapy for locally advanced cervical cancer was demonstrated through a single institutional experience with a small number of patients.